LA CRISE D’ « IDENTITÉ » DES SYSTÈMES D’INFORMATION DU SECTEUR PUBLIC - Najoua Farah (European Scientific Journal, ESJ, 2014)
The information system (I.S) in the public sector has several characteristics which require the establishment of an identity in line with its own specificities; however those systems suffer currently from an identity crisis caused particularly by its amalgamation with information systems of the private sector. This crisis that is compounded by focusing research on the private information systems, threatens good governance of those systems; one of measures that can be taken is toconstruct an academic body around the management of this technology in the public sector. Therefore the purpose of this research is to explore theoretically and practically the identity of those systems in order to demonstrate the issue of this assumed crisis.